How Much is a Little Girl Worth? - Denhollander, Rachael, 1984-; Huff, Morgan (Carol Stream, Illinois : Tyndale Kids/Tyndale House Publishers, Inc., 2019)
"This tenderhearted book teaches girls that they have immeasurable worth because they are made in the image of God. Armed with this understanding, girls will develop confidence in their own value and blossom into women who can face any challenge life puts in their path"--Provided by publisher.
Keywords: Girls -- Religious life; Juvenile literature; Self-esteem in children; Religious aspects; Juvenile literature; Self-reliance in children; Religious aspects; Juvenile literature; Self-confidence in children; Religious aspects; Juvenile literature; Self-esteem.; Self-reliance.; Self-confidence.